Consistency and reliability of judgements by assessors of case based discussions in general practice specialty training programmes in the United Kingdom. Issue 1 (2nd January 2017) - Bodgener, Susan; Denney, Meiling; Howard, John
Abstract: Case based discussions (CbDs) are a mandatory workplace assessment used throughout general practitioner (GP) specialty training; they contribute to the annual review of competence progression (ARCP) for each trainee. This study examined the judgements arising from CbDs made by different groups of assessors and whether or not these assessments supported ARCP decisions. The trainees selected were at the end of their first year of GP training and had been identified during their ARCPs to need extra training time. CbDs were specifically chosen as they are completed by both hospital and GP supervisors, enabling comparison between these two groups. The results raise concern with regard to the consistency of judgements made by different groups of assessors, with significant variance between assessors of different status and seniority. Further work needs to be done on whether the CbD in its current format is fit for purpose as one of the mandatory WPBAs for GP trainees, particularly during their hospital placements. There is a need to increase the inter-rater reliability of CbDs to ensure a consistent contribution to subsequent decisions about a trainee's overall progress.